The active site of the SGNH hydrolase-like fold proteins: Nucleophile–oxyanion (Nuc-Oxy) and Acid–Base zones - Konstantin Denessiouk; Alexander I. Denesyuk; Sergei E. Permyakov; Eugene A. Permyakov; Mark S. Johnson; Vladimir N. Uversky (Current Research in Structural Biology, 2024)
SGNH hydrolase-like fold proteins are serine proteases with the default Asp-His-Ser catalytic triad. Here, we show that these proteins share two unique conserved structural organizations around the active site: (1) the Nuc-Oxy Zone around the catalytic nucleophile and the oxyanion hole, and (2) the Acid-Base Zone around the catalytic acid and base. The Nuc-Oxy Zone consists of 14 amino acids cross-linked with eight conserved intra- and inter-block hydrogen bonds. The Acid–Base Zone is constructed from a single fragment of the polypeptide chain, which incorporates both the catalytic acid and base, and whose N- and C-terminal residues are linked together by a conserved hydrogen bond. The Nuc-Oxy and Acid-Base Zones are connected by an SHLink, a two-bond conserved interaction from amino acids, adjacent to the catalytic nucleophile and base.